Post-Pandemic Covid-19: Factors Affecting Startup Success in the Indonesian Economy - Ratih Damayanti; Andrie Yuswanto; Ahmad Hariri (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study aims to analyze the factors that influence the success of startups in helping the government increase economic growth during the Covid-19 pandemic. The Covid-19 pandemic had significantly impacted the economy, including Indonesia. Therefore, a solution is needed to improve the Indonesian economy. The variables in this study are